Mir-206 regulates pulmonary artery smooth muscle cell proliferation and differentiation. - Samuel Jalali; Gurukumar K Ramanathan; Prasanna Tamarapu Parthasarathy; Salman Aljubran; Lakshmi Galam; Asfiya Yunus; Sara Garcia; Ruan R Cox; Richard F Lockey; Narasaiah Kolliputi (PLoS ONE, 2012)
Pulmonary Arterial Hypertension (PAH) is a progressive devastating disease characterized by excessive proliferation of the Pulmonary Arterial Smooth Muscle Cells (PASMCs). Studies suggest that PAH and cancers share an apoptosis-resistant state featuring excessive cell proliferation. MicroRNA-206 (miR-206) is known to regulate proliferation and is implicated in various types of cancers. However, the role of miR-206 in PAH has not been studied. In this study, it is hypothesized that miR-206 could play a role in the proliferation of PASMCs. In the present study, the expression patterns of miR-206 were investigated in normal and hypertensive mouse PASMCs. The effects of miR-206 in modulating cell proliferation, apoptosis and smooth muscle cell markers in human pulmonary artery smooth muscle cells (hPASMCs) were investigated in vitro. miR-206 expression in mouse PASMCs was correlated with an increase in right ventricular systolic pressure. Reduction of miR-206 levels in hPASMCs causes increased proliferation and reduced apoptosis and these effects were reversed by the overexpression of miR-206. miR-206 over expression also increased the levels of smooth muscle cell differentiation markers α-smooth muscle actin and calponin implicating its importance in the differentiation of SMCs. miR-206 overexpression down regulated Notch-3 expression, which is key a factor in PAH development. These results suggest that miR-206 is a potential regulator of proliferation, apoptosis and differentiation of PASMCs, and that it could be used as a novel treatment strategy in PAH.